Bridge deck erection equipment : a best practice guide (ICE Publishing, 2018)
The bridge construction industry has moved with great speed towards mechanised construction solutions using specialised bridge deck erection equipment to shorten construction programmes and reduce costs. An increased level of knowledge related to these modern construction processes will ensure more efficient use of these methods, facilitate better decision-making processes and improve safety on site. In 'Bridge Deck Erection Equipment', international experts provide the industry with best practice advice and guidance to building bridge decks economically, practically and, above all, safely.
Previously issued in print in 2018. Digital resource published 2018.
Keywords: Bridges -- Floors -- Design and construction.; Bridges -- Design and construction -- Equipment and supplies.; elektronické knihy; electronic books